INFLUENCE OF TEACHER’S PREPARATION OF PROFESSIONAL DOCUMENTS ON STUDENTS’ ACADEMIC ACHIEVEMENT OF KISWAHILI LANGUAGE IN PUBLIC SECONDARY SCHOOLS IN KATHONZWENI SUB-COUNTY, KENYA - Kiamba, Elizabeth Welu; Mutua, Francis; Mulwa, David (Machakos University, 2019)
Poor performance in the Kenya Certificate of Secondary Education (KCSE) Examination has been of a great concern by all stakeholders particularly the students’ academic achievement of Kiswahili language. For five years Kathonzweni Sub County has been posting poor results in Kiswahili language. The purpose of the study was to establish the influence of teacher’s preparation of professional documents on students’ academic achievement in Kiswahili language. This study was guided by Teacher Efficacy theory. The study was conducted in Kathonzweni Sub County, Kenya. The target population comprised of 60 Kiswahili language teachers and 39 principals in all the 39 public secondary schools in the Sub County. The Kiswahili language teachers and the principals were purposively sampled. The sample size was all the 39 principals and 60 Kiswahili language teachers hence Census Survey. Questionnaires for principals and teachers were used as instruments of data collection. The objective of the study was; to establish the influence of the teacher’s preparation of professional documents on students’ academic achievement in Kiswahili language on students’ academic achievement in Kiswahili language in public secondary schools in the Sub County. Both questionnaires were piloted for reliability and yielded Chronbach Alpha Coefficient of 0.833 for principal’s questionnaire and 0.838 for teachers’ questionnaire. The data collected was quantitatively analyzed using Statistical package of Social Sciences (SPSS). Frequencies and percentages were used to summarize and describe data whereas Pearson correlation was used to establish relationships. The findings established that; teacher’s preparation of professional documents did not have a significant influence (r=0.273, p-value=0.649).The findings of the study will be useful in advising the Ministry of Education (MOE) on ensuring thorough grounding of teachers in teacher training colleges and universities to produce fully baked Kiswahili teachers. It may be used for future researches on related studies
Keywords: Teacher Preparedness; Student Achievement; Professional documents; Kiswahili Language